2021
DOI: 10.3390/healthcare9010080
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Rapid Strength Development and Muscle Stiffness in Older Population

Abstract: Background: Previous studies suggest that the capacity for rapid force production of ankle plantar flexors is essential for the prevention of falls in the elderly. In healthy young adults, there were significant associations between rate of force development and muscle stiffness measured by shear wave elastography. However, there has been no study investigating the association of rate of force development with shear elastic modulus in older adults. Methods: The muscle strength and shear elastic modulus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
3
3
1
Order By: Relevance
“…Foam rolling and the RM intervention have been shown to modify the myofascial viscoelastic properties by mechanisms, such as viscosity reductions, loosening of myofascial restrictions, fluid changes, and cellular responses (Cheatham and Stull, 2019;Kelly and Beardsley, 2016). Our study did not reveal significant changes in passive stiffness and shear elastic modulus, which is consistent with some of the previous studies (Krause et al, 2019;Nakamura et al, 2021a;Yoshimura et al, 2020). In contrast, other earlier trials showed that foam rolling decreases the passive stiffness of the anterior thigh (Wilke et al, 2019) or the shear elastic modulus of the hamstring (Morales-Artacho et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Foam rolling and the RM intervention have been shown to modify the myofascial viscoelastic properties by mechanisms, such as viscosity reductions, loosening of myofascial restrictions, fluid changes, and cellular responses (Cheatham and Stull, 2019;Kelly and Beardsley, 2016). Our study did not reveal significant changes in passive stiffness and shear elastic modulus, which is consistent with some of the previous studies (Krause et al, 2019;Nakamura et al, 2021a;Yoshimura et al, 2020). In contrast, other earlier trials showed that foam rolling decreases the passive stiffness of the anterior thigh (Wilke et al, 2019) or the shear elastic modulus of the hamstring (Morales-Artacho et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…As indicated, the results of the present study revealed increased DF ROM after a 180-second (three sets of 60-second) RM intervention, which is generally in accordance with previous works (Krause et al, 2019;Nakamura et al, 2021a;Wilke et al, 2019). However, in contrast to a recent meta-analysis (Wilke et al 2020), there were no significant sex differences.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No relationship between muscle stiffness and RFD in older people was found. 35 Changes in tendon stiffness can induce RFD discrepancies, but no such change has been demonstrated in CKD patients, presumably because the rate of force transmission through the tendon is extremely fast, requiring a considerably large change in the tendon structure to significantly disrupt RFD. 16,25 Human type-II muscle fibres are faster than type-I fibres.…”
Section: Discussionmentioning
confidence: 99%